2015
DOI: 10.1007/s00276-015-1595-4
|View full text |Cite
|
Sign up to set email alerts
|

The importance of intramedullary hip nail positioning during implantation for stable pertrochanteric fractures: biomechanical analysis

Abstract: In model situations, it has been shown that in stable fractures results do not depend on absolutely precise positioning and small deflections in the nails and neck screws positions do not significantly increase the risk of failure for the entire fixation. Damage to load-bearing structures relative to various implant placements does not impact the resultant overall fixation stability. Therefore, it is not necessary to re-introduce implants in the ideal position, which can lead to reduced patient radiation doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…While PFNA can generate bone compression around the helical blade because there are bone deficiencies in the femoral neck and femoral head after PFNA revision, which is more beneficial than DHS. This contradicts the findings of Baca et al [ 19 ]. They investigated the location of intramedullary hip screws for implantation in stabilized trochanteric fractures.…”
Section: Discussioncontrasting
confidence: 99%
“…While PFNA can generate bone compression around the helical blade because there are bone deficiencies in the femoral neck and femoral head after PFNA revision, which is more beneficial than DHS. This contradicts the findings of Baca et al [ 19 ]. They investigated the location of intramedullary hip screws for implantation in stabilized trochanteric fractures.…”
Section: Discussioncontrasting
confidence: 99%
“…16 The results of the present study also showed that when the lag screw is implanted in an inferior site, the femur experiences relatively lower stress and the implant experiences less displacement, thus agreeing with the results of previous studies. 5,14,15 These findings indicate that the TAD is not a primary predictor of implant failure. This concept is similar to the results of the above-mentioned study.…”
Section: Discussionmentioning
confidence: 84%
“… 13 Researchers have also used FEA to investigate the effects of different lengths and positions of the lag screw on proximal femoral nails and found that changing the length and implant position of the lag screw caused no significant difference. 14 In addition, the results of studies using FEA for assessment of stable intertrochanteric fractures showed that a lag screw position near the inferior posterior femoral head was a relatively ideal option. 15 In contrast, another FEA study of the stress distribution on the fracture line according to different lag screw positions demonstrated that the optimal lag screw position was at the middle portion of the femoral neck in stable intertrochanteric fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the ignorance of interaction between blade trajectory on the coronal and transverse planes was also a main limitation of this study [ 6 , 45 ]. However, for the lack of instant postoperative CT imaging data, the blade trajectory on the transverse plane can not be directly judged, and which should be identified in our future studies.…”
Section: Discussionmentioning
confidence: 99%